Lecturer Perceptions of Student Competence in Communicating during Teaching and Learning (Case Study at the Faculty of Social and Political Affairs, Gajah Putih University, Takengon) - Suknah (Formosa Journal of Social Sciences (FJSS), 2022)
Lecturers' Perceptions of Student Competence in Communicating During Teaching and Learning". The formulation of the problem in this research is how is the perception of Faculty of Social Sciences lecturers towards student competence in communicating, what media are used by lecturers in conveying lecture learning material. This study aims to identify how Faculty lecturers perceive Faculty of Social Sciences on student competence in communication, to analyze what media are used by lecturers in conveying lecture learning material.The research method in this study used qualitative research methods using observation, interview, and documentation techniques.In this study, the author used the theory of competence communication. From the results of this study it was found that the perceptions of lecturers of the Faculty of Social and Political Sciences towards student competence in communicating, namely the need for better communication improvements to students, the messages conveyed by students t ineffective, the message of the communicator (student) does not reach the communicant (listener) properly, some students still miss communication